2022
DOI: 10.32598/sija.2022.2183.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Education and Telephone Follow-Up on Care Burden of Caregivers of Older Patients with Stroke

Abstract: Objectives Stroke is the second leading cause of death and the third leading cause of disability worldwide. Caregivers of stroke patients experience high levels of care burden that can affect their physical and psychological health. It is necessary to use interventional programs for family caregivers to prevent or reduce their care burden. This study aims to determine the effect of education and telephone follow-up on care burden of the family caregivers of older patients with stroke. Methods & Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…There is also a considerable difference between the burden of care before and after the intervention (p<0.05) so that patients' average quality of life reaches 11.08-13.61, and the moderate pressure of care burden goes 2.27-3.78 after the intervention. Sixth article (Ardalan et al, 2022) The research design used was a randomized controlled clinical trial. This study aimed to determine the effect of education and telephone follow-up on the burden of caring for family caregivers in elderly stroke patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a considerable difference between the burden of care before and after the intervention (p<0.05) so that patients' average quality of life reaches 11.08-13.61, and the moderate pressure of care burden goes 2.27-3.78 after the intervention. Sixth article (Ardalan et al, 2022) The research design used was a randomized controlled clinical trial. This study aimed to determine the effect of education and telephone follow-up on the burden of caring for family caregivers in elderly stroke patients.…”
Section: Resultsmentioning
confidence: 99%
“…This study aimed to determine the effect of education and telephone follow-up on the burden of caring for family caregivers in elderly stroke patients. In research (Ardalan et al, 2022) before the intervention, there was no significant difference between the two groups in the amount of care burden (26.20 + 11.08 for the intervention group and 28.70 + 11.63 for the control group) (p=0.333); however, after the intervention, the intervention group's care burden (18.28 + 10.07) and control group (29.80 + 11.76) showed a significant difference (p<0.001). The results showed that 12 weeks of education and telephone follow-up significantly reduced the caregiver's family care burden (p<0.001).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, telehealth can assist more senior people in following their exercise delivery during the pandemic, and it is potentially more effective in addressing the needs of older adults in remote areas [80]. Interventions through education and telephone follow-up can also reduce the burden of care of caregivers of older adults [85]. Nursing students were reported to have sufficient confidence in using telemedicine for frail people during the pandemic, and they confirmed its validity and importance [86].…”
Section: Social Supportmentioning
confidence: 95%